Development of Flashcard Media on Reproductive System Material to Enhance Highschool Students' Higher-Order Thinking Skills - Mega Wahyuni Nasution; Efrida Pima Sari Tambunan (IKIP Mataram, 2024)
The study focuses on the development of Flashcard learning media for the reproductive system, with the aim of improving high school students' higher-order thinking skills (HOTS) through valid, practical, and effective means. The research adopts the Research and Development (R&D) approach, utilizing the 4D development model, which includes the Define, Design, Development, and Dissemination phases. The research participants consist of experts in the field of reproductive system materials, media experts, subject teachers, and grade eleven students, totaling 35 individuals. The research employs interviews, questionnaires, and written tests in the form of pretest and posttest questions, with a focus on higher-order thinking skills, comprising a total of ten questions. The results of the study indicate that the material expert validation attained a percentage of 85.71%, signifying a highly feasible category. Similarly, the media experts obtained a score of 98.43%, also falling under the highly feasible category. The practicality assessment from the teachers yielded a score of 90.90%, indicating high practicality, while the students' practicality assessment achieved a score of 89.74%, also signifying high practicality. The effectiveness of the N-Gain Score was determined to be 0.65, indicating a fairly effective outcome. Based on these findings, it can be concluded that the development of Flashcard learning media is valid, practical, and effective.